EVALUATION OF SELECTED PROPERTIES OF COMMERCIAL AND DEVELOPED LIQUID SOAPS (The Research of Medical Science Review, 2025)
Background: Frequent washing of hands is advisable by W.H.O (World Health Organization) to eradicate transmission of germs with suitable suds (soap). However, on frequent washing people experience dryness of hands in absence of proper quantity of humectant / lubricant in soap. Objective: Inexpensive liquid soap is affordable and available to individuals of different financial levels. Producing low-cost soap frequently demands fewer resources and energy. During this research authors tried to eliminate risks associated with use of more chemicals and evaluated formulations in terms of organoleptic properties. Methods: In present study two different formulations of liquid soaps are prepared by using castor oil and glycerin to avoid dryness. Comparison is made on selected parameters of liquid soaps with three commercially available similar products. The findings of this study revealed that customers have occasionally suffered unfavorable outcomes after consuming synthetic chemicals. Results: Although properties of lab-made liquid soaps are not same as market soaps but some parameters including density (F1 is 0.830 and F2 is 0.821), acidity level (pH of F1 and F 2 is 5.4 and 4.9 respectively), spread ability, flow-ability and stability in volume of foam are comparable. Additionally, adjust pH roughly 5.5 to ensure skin safety and comfort. Finally, strive for viscosity that is appropriate for liquid soap, making it easy to dispense and apply. By harmonizing these critical criteria, an economical, good-quality liquid soap is developed that also matches requirements of consumers. Conclusion: The conclusion of current study is to create cost-effective liquid soap with streamlined composition that promotes simplicity, efficacy, and skin safety. Formulation was focused to be developed with a minimum number of ingredients, utilizing affordable and commonly available components. Liquid soap should be highly effective while keeping skin soft.